2005
DOI: 10.1111/j.1553-2712.2005.tb01545.x
|View full text |Cite
|
Sign up to set email alerts
|

Observational Study of Intravenous versus Oral Corticosteroids for Acute Asthma: An Example of Confounding by Severity

Abstract: In this observational study, patients with worse asthma exacerbations were more likely to receive IV corticosteroids as compared with oral corticosteroids. Although we controlled for many markers of asthma severity, we were unable to completely control for baseline differences between the IV and oral corticosteroid groups. Observational research continues to serve as an important tool for describing problems and for understanding many exposure-disease associations. For examining the impact of treatments on adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The apparent increased risk of admission among patients with an AP does not imply a causal relationship. One must keep in mind confounding by severity (28); in a non-randomized study, it is likely that only the most severely ill patients with APs actually presented to the ED. Randomized trials have demonstrated that APs reduce morbidity and use of medical services (26).…”
Section: Discussionmentioning
confidence: 99%
“…The apparent increased risk of admission among patients with an AP does not imply a causal relationship. One must keep in mind confounding by severity (28); in a non-randomized study, it is likely that only the most severely ill patients with APs actually presented to the ED. Randomized trials have demonstrated that APs reduce morbidity and use of medical services (26).…”
Section: Discussionmentioning
confidence: 99%
“…Anticoagulation data were extracted from pharmacy billing files and included hospital day of administration, quantity, route, and dosing. To attenuate unmeasured confounding by illness severity owing to patients’ ability to take oral anticoagulant medications during sepsis, 15 we restricted our definition of anticoagulant exposure in the primary analysis to initial use of parenteral intravenous or subcutaneous administration of anticoagulants in doses greater than those used for prophylaxis of venous thromboembolism (ie, intravenous heparin sodium, >20 000 U daily, subcutaneous enoxaparin sodium twice daily [total daily dose >80 mg], subcutaneous dalteparin sodium, >5000 IU daily, and fondaparinux sodium, >2.5 mg daily). We allowed for oral anticoagulants (eg, warfarin sodium) later during hospitalization among patients who received an intravenous or subcutaneous anticoagulant initially, but excluded patients who received oral anticoagulants as their initial anticoagulant in the primary analysis.…”
Section: Methodsmentioning
confidence: 99%
“…We adopted two approaches, restriction of our sample and propensity score analysis, to address potential confounding by severity. Confounding by severity is a potential bias particularly relevant to observational studies of medication treatment that has been most thoroughly explored in the pulmonary and cardiology literature (e.g., Beasley et al 1994;Clark et al 2005;Garrett et al 1996). In our study, confounding by severity refers to the phenomenon whereby individuals who are the most severely ill and least likely to work are more likely to come to the attention of prescribers and receive medication, thus potentially distorting the relationship between medication and work.…”
Section: Introductionmentioning
confidence: 93%